Segmental congenital cutaneous smooth muscle hamartoma. Case report. - Neri, I.; Patrizi, A.; Rizzoli, L.; Trestini, D. (European Journal of Pediatric Dermatology, 1998)
Cutaneous smooth muscle hamartoma (CSMH) is characterized by a proliferation of smooth muscle fibers. The congenital variant usually presents with a hyperpigmented patch, which is covered by hairs, sometimes associated with follicular micropapules. The hamartoma is more frequently localized on the lumbar region or on the roots of the limbs. Different clinical variants were reported. The Authors reported a case of congenital CSMH of the trunk with metameric distribution, which was characterized by a hypertrichosis patch arising on normally pigmented skin and discussed the differential diagnosis from circumscribed nevoid hypertrichosis.